Long-term Results of Endonasal Endoscopic Transsphenoidal Resection of Nonfunctioning Pituitary Macroadenomas. Issue 1 (24th September 2014) - Dallapiazza, Robert F.; Grober, Yuval; Starke, Robert M.; Laws, Edward R.; Jane, John A.
Abstract: BACKGROUND: Several studies report early results of endoscopic endonasal transsphenoidal surgery; however, none discuss long-term outcome measures such as tumor recurrence rates and the need for additional surgical procedures. OBJECTIVE: To discuss the long-term outcomes after endoscopic endonasal transsphenoidal surgery for nonfunctioning pituitary macroadenomas. METHODS: This is a retrospective study. Patients were included only if they had at least 5 years of clinical and imaging follow-up after surgery. RESULTS: Eighty patients met the study criteria. Grossly complete resection was achieved in 71% of patients. Knosp grade 0 to 2 tumors and tumor with volumes <10 cm 3 were significantly more likely to have received a grossly complete resection. There were 7 recurrences (12%) in patients who had received grossly complete resections, with a mean time to recurrence of 53 months. Among the 23 patients who had subtotal resections, 11 (61%) progressed radiographically, and 3 (17%) had symptomatic progression. Knosp score, surgical and radiographic evidence of invasion, and preoperative visual deficits were predictive of recurrence in a univariate analysis, but Knosp grade was the only independent predictor in a multivariate analysis. Kaplan-Meier analysis projected a 10-year progression-free survival rate of 80% and 21% for patients with gross total resections and subtotal resections, respectively. CONCLUSION: At the long-term follow-up, 12% of patients had recurrent tumors after grossly complete resection. Recurrent or residual tumors were treated with either repeat surgery or Gamma Knife radiosurgery. Rates of complete resection, postoperative surgical and endocrinological complications, and additional surgical procedures are similar to previously published reports after microscopic transsphenoidal surgery.